2014
DOI: 10.2134/agronj13.0233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐Term Fertilization on Soil Carbon and Nitrogen in Chinese Mollisols

Abstract: ree eld experiments were conducted to examine the in uence of long-term (30-31 yr) e ect of fertilizer applications on soil C and N in the mollisols of Northeast China. Each experiment represented a di erent latitude range: low latitude (LatL), middle latitude (LatM) and high latitude (LatH). Four types of fertilizer applications were considered: (i) CK: unfertilized (control); (ii) NPK: balanced application of inorganic fertilizer nitrogen, phosphorus, potassium; (iii) M: application of organic manure; and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Consistent with the previous studies (Jiao et al ., ; Wang et al ., ,b), our results showed that changes in soil C and N contents were the main factors that affect the plant–microbe networks. From the standpoint of soil C content, soil microbes such as bacteria and fungi mainly rely on the large amounts of sugars, amino acids and organic acids deposited in the plant rhizosphere (Bais et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous studies (Jiao et al ., ; Wang et al ., ,b), our results showed that changes in soil C and N contents were the main factors that affect the plant–microbe networks. From the standpoint of soil C content, soil microbes such as bacteria and fungi mainly rely on the large amounts of sugars, amino acids and organic acids deposited in the plant rhizosphere (Bais et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The combined application of organic and inorganic fertilizers reduced C emissions compared with the sole application of organic fertilizer. This was because it improved the immobilization of active C (e.g., microbial biomass C, readily oxidizable C) [43][44][45]. Thus, the results of this study showed that CO 2 emissions under microbial fertilizers application are reduced significantly (Figure 6).…”
Section: 2mentioning
confidence: 64%
“…To a large extent, this was because JS promoted the decomposition of straw without nitrogen fixation. Previous studies [44,45] reported that the combined application of organic and inorganic fertilizers enhanced the activity of organic C and N and the immobilization of ammonium N. This equally explained why N 2 O emissions under ETS were lower than those under the JS treatment, as organic matter in ETS enhanced N fixation. Additionally, microbial fertilizer can also alter soil denitrification by changing the functional gene of denitrifying agents [56,57], which could limit N 2 O flux with the application of microbial fertilizer.…”
Section: 2mentioning
confidence: 80%
“…However, for decades, predatory development and the heavy use of nutrients have led to a long-term excess of CF inputs. Agricultural surface pollution and soil consolidation problems are becoming increasingly serious, the ecological environment continues to deteriorate, the black soil layer is thinning, and the soil organic matter content is declining rapidly [76,77]. In addition, with the increasing level of urbanization, the rural population of Jilin Province has been flowing out so it has decreased from 12.9 million in 2005 to 11.23 million in 2019.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%